Figure 2 from: Fernandez-Triana J (2014) New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. Biodiversity Data Journal 2: e1040. https://doi.org/10.3897/BDJ.2.e1040 - Fernandez-Triana, Jose (Zenodo, 2014)
Figure 2 - Microgaster deductor specimen from Churchill, Manitoba. Red arrows show a lobed tarsal claw and the ovipositor sheaths. Frontal view of head modified from Nixon (1968).